2019
DOI: 10.1177/2047487319843068
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep duration, sleep quality and hyperlipidemia in middle-aged and older Chinese: The Dongfeng–Tongji Cohort Study

Abstract: Aims This study aimed to evaluate the relationship between sleep duration, sleep quality and hyperlipidemia in middle-aged and older Chinese. Methods We included 20,712 individuals at baseline from September 2008 to June 2010, and they were followed-up until October 2013. Hyperlipidemia was defined according to the Chinese guidelines on the prevention and treatment of dyslipidemia in adults. Sleep duration was self-reported and sleep quality was evaluated with a questionnaire that was designed according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Consideration of anemia has been recommended as part of the clinical evaluation of patients with insomnia. As for hyperlipidemia, long sleep duration has been reported to be associated with higher risk of hyperlipidemia [41], while some studies observed positive association between short sleep duration and high TG or TC levels [42]. In our study, short sleeping habits may predispose individuals to hyperlipidemia risk.…”
Section: Discussionmentioning
confidence: 45%
“…Consideration of anemia has been recommended as part of the clinical evaluation of patients with insomnia. As for hyperlipidemia, long sleep duration has been reported to be associated with higher risk of hyperlipidemia [41], while some studies observed positive association between short sleep duration and high TG or TC levels [42]. In our study, short sleeping habits may predispose individuals to hyperlipidemia risk.…”
Section: Discussionmentioning
confidence: 45%
“…Hyperlipidaemia refers to a systemic metabolic disorder in which the concentration of total cholesterol (TC) and triglyceride (TG) in plasma significantly increase due to abnormal fat metabolism or fat transport [1]. Subtypes of hyperlipidaemia include hypercholesterolaemia and hypertriglyceridaemia.…”
Section: Introductionmentioning
confidence: 99%
“…[41] Consideration of anemia has been recommended as part of the clinical evaluation of patients with insomnia. As for hyperlipidemia, long sleep duration has been reported to be associated with higher risk of hyperlipidemia, [42] while some studies observed positive association between short sleep duration and high TG or TC levels [43]. In our study, short sleeping habits may predispose individuals to hyperlipidemia risk.…”
Section: Discussionmentioning
confidence: 45%